Novel Mutation Sites in the Development of Vancomycin- Intermediate Resistance in Staphylococcus aureus - Wang, Yubing; Li, Xiaoli; Jiang, Libo; Han, Wentao; Xie, Xiangming; Jin, Yi; He, Xiaoqing; Wu, Rongling (Frontiers in Microbiology, 2017)
Increased use of vancomycin has led to the emergence of vancomycin-intermediate Staphylococcus aureus (VISA). To investigate the mechanism of VISA development, 39 methicillin-susceptible strains and 3 MRSA strains were treated with vancomycin to induce non-susceptibility, and mutations in six genes were analyzed. All the strains were treated with vancomycin in vitro for 60 days. MICs were determined by the agar dilution and E-test methods. Vancomycin was then removed to assess the stability of VISA strains and mutations. Following 60 days of vancomycin treatment in vitro, 29/42 VISA strains were generated. The complete sequences of rpoB, vraS, graR, graS, walK, and walR were compared with those in the parental strains. Seven missense mutations including four novel mutations (L466S in rpoB, R232K in graS, I594M in walK and A111T in walR) were detected frequently in strains with vancomycin MIC ≥12 µg/mL. Jonckheere-Terpstra trend test indicated these mutations might play an important role during VISA evolution. After the vancomycin treatment, strains were passaged to vancomycin-free medium for another 60 days, and the MICs of all strains decreased. Our results suggest that rpoB, graS, walK and walR are more important than vraS and graR in VISA development.